Sigla (Sigla_V_XXVIII) - Robinson, James M. (BrillOnline Reference Works, 2012)
Sublinear dots beneath letters in the transcription indicate that the letters so marked are not visually certain. Dots appearing on the line outside of brackets indicate illegible Coptic letters. Each dot represents one letter. Dots appearing on the line inside of brackets in the transcription represent the number of Coptic letters it is calculated are missing in the lacuna. Each dot represents one letter